Measurement of Heat Transfer Rates of Polypropylene and Cotton Nonwoven Fabrics via Thermal Conduction - El Arabi ,, S. M.; M., Fatima (Gezira Journal of Engineering and Applied Sciences, 2018)
Industrial textiles are widely being used for different simple and complex applications. Two samples of nonwoven fabrics were used in this study to assess their ability to transfer heat. They were made of polypropylene and carded cotton web. A simple model consisting of three 1×1 m 2 brick rooms was used having two of them being coated from inside by the samples using a polymeric adhesive. The third room was left blank. The outdoors and the conjugated indoors temperature degrees, at different periods of time during the day, were measured and recorded. A mathematical correlation was carried out. The samples showed delayed heat transfer rates compared to the untreated room, which indicates better insulation properties. On the other hand the cotton carded web fabric was even better than the polypropylene fabric.